A route to robust thioether-functionalized MOF solid materials displaying heavy metal uptake and the ability to be further oxidized. Issue 36 (30th August 2017) - Xiao, Guo-Wei; Chen, Teng-Fei; Sun, Xin-Zhan; Guo, Hui; Li, Zhong-Feng; Deng, Yu-Heng; Wan, Chong-Qing
Abstract : A facile and mild solvent-assisted ligand exchange method was developed as an alternative strategy to achieve thioether-based MOFs, and their oxidized forms, that were able to take up heavy metals from solutions and capture CO2 . Abstract : Here we developed a facile solvent-assisted ligand exchange method for synthesizing thioether-containing hybrid metal–organic frameworks (MOFs) that cannot be made using direct synthesis. Such a tailored approach provides an alternative method to achieve thioether-based MOFs and its oxidation-decorated materials. These materials showed the ability to take up heavy metals from solution and the ability to capture CO2 .